To solve the equation \(5(2x + 2) - 4 = 2x + 6\), we can start by expanding and simplifying both sides.
-
Expand the left side: \[ 5(2x + 2) - 4 = 10x + 10 - 4 = 10x + 6 \]
-
Rewrite the equation: \[ 10x + 6 = 2x + 6 \]
-
Subtract \(2x\) from both sides: \[ 10x - 2x + 6 = 6 \] This simplifies to: \[ 8x + 6 = 6 \]
-
Subtract 6 from both sides: \[ 8x = 0 \]
-
Divide by 8: \[ x = 0 \]
Now we check the solution:
Substituting \(x = 0\) back into the original equation:
Left side: \[ 5(2(0) + 2) - 4 = 5(0 + 2) - 4 = 5 \cdot 2 - 4 = 10 - 4 = 6 \]
Right side: \[ 2(0) + 6 = 0 + 6 = 6 \]
Both sides equal 6, confirming that our solution \(x = 0\) is correct.
Since we found one unique solution, the answer is:
The equation has one solution: x=0.